Fibrous bands associated with higher Masaoka stage and poor recurrence‐free survival in patients with thymoma. Issue 3 (25th November 2020) - Minami, Kazuhiro; Jimbo, Naoe; Tanaka, Yugo; Uchida, Takahiro; Okamoto, Takeshi; Shimizu, Nahoko; Doi, Takefumi; Hokka, Daisuke; Itoh, Tomoo; Maniwa, Yoshimasa
Abstract : Background: Fibrous bands (FBs) are one of the histological features in tumors which can be confirmed by hematoxylin and eosin (H&E)‐stained slides. FBs have been reported to correlate with malignancy in various tumors. This study aimed to investigate whether the presence of FBs is associated with malignancy in thymoma. Methods: A total of 123 consecutive patients with thymoma who underwent microscopically complete resections from January 2000 to December 2018 were enrolled into this study. H&E‐stained slides of all thymoma patients were re‐examined. Study patients were classified into two groups: with FBs ( n = 36) and without FBs ( n = 87). Clinicopathological characteristics, overall survival (OS), and recurrence‐free survival (RFS) were compared between the two groups. Furthermore, multivariate analyses were performed to identify whether the presence of FBs was associated with higher Masaoka stage and poor prognosis in patients with thymoma. Results: The Masaoka stage was found to be higher and recurrence more likely in thymoma patients with FBs than in those without. RFS was significantly poorer in thymoma patients with FBs than in those without, although no significant difference was observed in OS between them. The presence of FBs was significantly associated with higher Masaoka stage in the multivariate analysis using logistic regression. Additionally, the presence of FBs was an independent prognostic factor for poor RFS in multivariate analysis using Cox's proportional hazards model. Conclusions: The presence of FBs in patients with thymoma was associated with higher Masaoka stage, higher recurrence rate, and poorer RFS. Key points: Significant findings of the study: Fibrous bands (FBs) are bands of fibrosis dividing tumors into different‐sized irregular islands. The presence of FBs is associated with higher Masaoka stage and poor recurrence‐free survival in patients with thymoma. What this study adds: The presence of fibrous bands might be associated with the malignant behavior of thymoma. Confirming the presence or absence of FBs may result in personalized medication for patients with thymoma. Abstract : Fibrous bands (FBs) are bands of fibrosis dividing tumors into different‐sized irregular islands. The presence of FBs is associated with the malignant behavior of thymomas. Confirmation of FBs might lead to individualized medications in patients with thymoma.